Tool to determine vehicle ground lines - Mohd Redza, Abdul Razak (2008)
Before completing the design of a car, the ground lines position must be determined to determine the other position and design of part of a car. The ground lines consist of three lines which is the curb line, design line and the Gross Vehicle Weight line (GVW). The ground lines position is essential to be determined at the beginning of a project due to the influence on design and styling. The first method of determining the position of the ground lines is to identify and research on the factors that need to be analyze first before the position of the ground lines is obtained. These factors are used to calculate the ground lines position. The existing of program will assist the design engineers’ team to calculate the ground lines position faster and save time to calculate the ground lines position. The formulation is then modelled in Microsoft Visual Studio.net to build a program that will function as a tool to calculate the vehicle ground lines position. The data to test the formulation for this project was taken from the Proton Persona 1.6. The result obtained was then compared with the real published data to check the accuracy of the ground lines calculation program. Then the obtained ground clearance from this program is compared with the data from the Proton Persona 1.6 brochure. After the comparison, the program is proved to be sufficient to estimate the ground lines position.